2017
DOI: 10.5897/ajb2017.16044
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of thermostable and alcohol tolerant lipase from Pseudoxanthomonas sp.

Abstract: An extracellular lipase from Psedoxanthomonas sp. was purified 47.3 folds with an overall yield of 27% through purification procedure of acetone precipitation, ion exchange and gel filtration chromatography. Protein precipitation using acetone fractionation showed that the enzyme was precipitated at the fraction of 0 to 40%. Further purification of the enzyme by ion exchange followed by gel filtration chromatography showed that there were two types of lipases with similar molecular size at around 50 kDa. Chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Our previous report showed that lipase from Pseudoxantomonas sp. still exhibited an activity in the presence of methanol up to 30 % concentration [ 37 ]. Furthermore, lipase from Geobacillus thermoleovorans showed tolerance to various polar solvents and loss of activity in the presence of n-hexane and chloroform [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous report showed that lipase from Pseudoxantomonas sp. still exhibited an activity in the presence of methanol up to 30 % concentration [ 37 ]. Furthermore, lipase from Geobacillus thermoleovorans showed tolerance to various polar solvents and loss of activity in the presence of n-hexane and chloroform [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that the maximum activity at pH 9 ( Fig. 3), suggested that the enzymewas an alkali tolerant lipase 10,13 . The high activity of the isolated at alkaline condition suggests that the lipase shows high potential application on many industries such as detergent, biopolymers, pharmacy, cosmetics and flavor 17 .…”
Section: Characterization Of Theenzymementioning
confidence: 93%
“…Isolate AL89 was inoculated in 100 mL media (0.1% CaCl 2 , 0.5% yeast extract, 0.5% meat extract, 0.1% NaCl in 0.05 M phosphate buffer pH 8.0),then incubated at 55 o C 150 rpm for 19 hours, as was done in a previous study 13 . Extracellular lipase was obtained from culture supernatants which had been centrifuged for 45 minutes at 12000 g.…”
Section: Crude Extract Productionmentioning
confidence: 99%
See 2 more Smart Citations